Intenção empreendedora, inovação e sustentabilidade: uma abordagem cross-cultural - Paiva, Luis Eduardo Brandão (2022)
This thesis is organized from the construction of three scientific articles, which cover thematic fields related to entrepreneurial intention, sustainability, and innovation, in an attitudinal-intentional perspective. The central questioning of the thesis focuses on the possible existing relationships and on the impacts of sustainability and innovation on entrepreneurial intention, with a cross-cultural approach between individuals from Brazilian and Spanish universities. From this, the general aimed of the thesis was to analyze the relationships and impacts of sustainability and innovation on entrepreneurial intention. Some theoretical and methodological approaches were adopted on the themes investigated: (i) sustainability, with an emphasis on environmental awareness and on the attitude and orientation towards sustainability in the context of entrepreneurship; (ii) innovation, through the Adaptation-Innovation Theory; and (iii) entrepreneurial intention, based on the Theory of Planned Behavior. Data analyzes were established in two ways: (a) carrying out a systemic search in the Scopus database; and (ii) application of questionnaires to university students from Brazilian and Spanish universities. The research is based on the positivist paradigm, presenting a quantitative approach, with a descriptive and explanatory nature. The data analysis techniques adopted were: Bibliometric Network Analysis, Chi-Square Test, t and Mann-Whitney Tests, Exploratory Factor Analysis, Logistic Regression and Structural Equation Modeling (Permutation and Multigroup Analysis). Data treatment was supported by software: VOSViewer®, Statistical Package for Social Sciences (SPSS®) and SmartPLS®. The results of the thesis, broken down into three scientific articles, showed, as for the first study, which investigated the international scientific production on entrepreneurial intention and sustainability, that the literature dealing with the alignment between entrepreneurial intention and sustainability is still incipient, being emerging themes correlated to entrepreneurial intention and sustainability were found: entrepreneurial education and gender; sustainable practices; innovation and personality traits; intention, sustainable entrepreneurship and social entrepreneurship. These results suggest the need for the development of research that address the social, economic, and political context in Brazil and in the world. For scientific article 2, which analyzed the influence of innovative and sustainable behavioral constructs on the entrepreneurial intention of university students across different countries, it was verified that the constructs of the Theory of Planned Behavior (personal attitudes and perceived behavioral control) influenced the entrepreneurial intention of individuals, with the exception of subjective norms; and yet they proved to be more innovative than adaptive - depending on the alignment between Adaptation-Innovation Theory and entrepreneurial intention. However, environmental awareness, through sustainable behavioral constructs, was not influential in predicting the entrepreneurial intention of students from Brazilian and Spanish universities. Scientific article 3 focused on investigating the relationships between sustainability and innovation in the entrepreneurial intention of students from Brazilian and Spanish universities. This study allowed us to point out that there are relationships between the constructs of the Theory of Planned Behavior (personal attitudes, subjective norms, and perceived behavioral control) and that, despite attitudes towards sustainability having impacted on the intention to undertake, in terms of social and environmental concern, the fact that individuals are sustainably oriented can be an impediment for them to undertake. Furthermore, the propensity to innovate was also a strong predictor of entrepreneurial intent among individuals at both universities. It is understood, based on the development of this thesis, that there are contributions that reinforce the originality and originality, emphasizing, a priori, that the bibliometric approach contributed to the systematization of scientific knowledge about entrepreneurial intention and sustainability, given the fact that those scientific publications show trends and influences in the most diverse areas of scientific knowledge. As the entrepreneurial intention is relevant today, this thesis also had the contribution of seeking to impact on the encouragement of policies and practices aimed at Higher Education Institutions in different countries, especially to broaden understandings, views and knowledge about the importance of studies and practices environmental, innovative and social in line with the entrepreneurial context - with the aim of enhancing the social and environmental benefits generated by entrepreneurs, as well as by future entrepreneurs.